Mapping the landscape of integrated reporting study: A systematic literature review approach - Nugraha, Erik; Djajadikerta, Hamfri; Fettry, Sylvia (Edelweiss Applied Science and Technology, 2025)
Integrated reporting is an evolution of corporate reporting whose aim is to support the implementation of sustainable strategies. It is hoped that it can help organizations provide a more holistic view of their business by offering a clear picture of all the capital they have that is directed towards long-term value creation. The research aims to determine the theoretical basis for research on integrated reporting, as well as the factors influencing the adoption of integrated reporting. The method used in this research is a Systematic Literature Review, following the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA), using data sources originating from scientific publications indexed in the Scopus database. Based on the literature extraction process in accordance with the selection criteria, 30 journal articles were obtained for analysis in line with the research questions. The research results show that the theoretical basis used in research on the topic of integrated reporting is dominated by the use of agency theory and stakeholder theory, while the factors or determinants that influence the adoption of integrated reporting can be categorized into two groups: (1) Internal factors and (2) External factors.